The Ultimate in Verbalization: How Japanese Writer Furui Yoshikichi Reads Western Mystical Experiences - Seungjun Lee; Do-Hyung Kim (Religions)
This study examines how the Japanese writer Furui Yoshikichi engages with Western mystical experiences, particularly through his reading of Martin Buber’s Ecstatic Confessions and his broader engagement with Meister Eckhart and medieval German mysticism. Furui’s literary inquiry revolves around the inherent tension between the ineffability of mystical experiences and their articulation through language. He critically engages with the paradox of verbalization, recognizing that while mystical experiences transcend linguistic and temporal boundaries, they nevertheless achieve resonance through written and spoken expressions. His reflections converge with Buddhist notions of Sūnyatā, underscoring intersections between Eastern and Western spiritual traditions. Drawing upon his background as a translator of German literature, Furui mediates mystical experiences within a comparative framework, navigating cultural and linguistic boundaries. His approach elucidates the concept of the multiplicity of qualities in mystical experiences, demonstrating particularity and universality simultaneously. By analyzing Furui’s interpretation of mystical texts, this study contributes to broader discussions on the limitations of language in conveying transcendence and the role of literary imagination in rendering the ineffable.